2014
DOI: 10.15804/tner.14.37.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Metacognitively: Metacognitive Skills and Science Performance

Abstract: The presented study aims to identify the relations between metacognitive skills and science performance. Data were collected from 211 Romanian adolescents in the seventh and eighth grades, who completed the Junior Metacognitive Awareness Inventory (the version for 5th- 9th grades). The results indicate that adolescents generally use metacognitive skills when learning science subjects and that some metacognitive skills are associated with better performance in science. Nevertheless, adolescents seem to encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A study by [22] found that critical thinking dispositions significantly influenced the level of entrepreneurship, and there were notable differences in CCTDI (California Critical Thinking Inventory) scores among different student groups based on gender, high school, and departmental variables. Similarly, [24] showed that the disposition of critical thinking was positively associated with the meaning of life in individuals. Based on these findings, the following research hypotheses are suggested: H1.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…A study by [22] found that critical thinking dispositions significantly influenced the level of entrepreneurship, and there were notable differences in CCTDI (California Critical Thinking Inventory) scores among different student groups based on gender, high school, and departmental variables. Similarly, [24] showed that the disposition of critical thinking was positively associated with the meaning of life in individuals. Based on these findings, the following research hypotheses are suggested: H1.…”
Section: Methodsmentioning
confidence: 98%
“…What is the relationship between critical thinking and human logic? How does formal education in Romania influence the development of critical thinking [24]? This study aims to explore how critical thinking affects academic performance.…”
Section: Methodsmentioning
confidence: 99%
“…Using metacognitive knowledge and skills in learning allows us to search for, select and evaluate information, choose, and assess learning strategies, and be aware of our learning strengths and weaknesses. Research shows that students who use metacognition better understand essential scientific concepts and processes and have higher positive attitudes towards science compared to those who do not use metacognition during the learning process (Ciascai & Haiduc, 2014;Jahangard et al, 2016;Mai, 2015;Wirzal. et al, 2022;Tsai.…”
Section: Introductionmentioning
confidence: 99%